Pengaruh Kualitas Produk Dan Strategi Promosi Terhadap Minat Beli Konsumen - Alamulhuda Al mubarok (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This study aims to determine the Simultaneous and Partial Effects between Product Quality and Promotional Strategies on Consumer Buying Interest (Survey on wedding photography and videograph vendors Hillostory Tasikmalaya). The research method used is a survey method with a quantitative approach. The sample used is 40 respondents. The data used are primary data and secondary data. The technique used in data collection using a questionnaire. The analytical tool used in this study is multiple regression using SPSS 25. The results of the study show that simultaneously product quality and promotional strategies have a significant effect on consumer buying interest. Partially, product quality has a significant effect on consumer buying interest. Partially the promotion strategy has an effect on consumer buying interest.